ESCAPS study protocol: a feasibility randomised controlled trial of ‘Early electrical stimulation to the wrist extensors and wrist flexors to prevent the post-stroke complications of pain and contractures in the paretic arm’ - Fletcher-Smith, Joanna C.; Walker, Dawn-Marie; Sprigg, Nikola; James, Marilyn; Walker, Marion F.; Allatt, Kate; Mehta, Rajnikant; Pandyan, Anand D. (BMJ Publishing Group, 2016)
Introduction Approximately 70% of patients with stroke experience impaired arm function, which is persistent and disabling for an estimated 40%. Loss of function reduces independence in daily activities and impacts on quality of life. Muscles in those who do not recover functional movement in the stroke affected arm are at risk of atrophy and contractures, which can be established as early as 6 weeks following stroke. Pain is also common. This study aims to evaluate the feasibility of a randomised controlled trial to test the efficacy and cost-effectiveness of delivering early intensive electrical stimulation (ES) to prevent post-stroke complications in the paretic upper limb.